2015
DOI: 10.1108/jrf-06-2014-0085
|View full text |Cite
|
Sign up to set email alerts
|

Debt financing and firm performance: an empirical study based on Swedish data

Abstract: Purpose – The purpose of this study is to examine the relationship between debt level and performance among small and medium-sized enterprises (SMEs). Design/methodology/approach – Unlike the vast majority of previous research, this study uses three-stage least squares (3SLS) and fixed-effects models to analyse a comprehensive, cross-sectoral sample of 15,897 Swedish SMEs operating in five industry sectors during the 2009-2012 period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
134
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(166 citation statements)
references
References 47 publications
28
134
3
1
Order By: Relevance
“…The coefficient of TDR in model 2 was β = −0.744, with a statistical significance at the 1% level. Debt financing had a statistically significant and negative impact on economic performance (ROA and SGR) that was consistent with Barry and Mihov (2015) [15] and Yazdanfar and Öhman (2015) [16]. This result supports Hypothesis 1.…”
Section: Tests Of Hypotheses and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The coefficient of TDR in model 2 was β = −0.744, with a statistical significance at the 1% level. Debt financing had a statistically significant and negative impact on economic performance (ROA and SGR) that was consistent with Barry and Mihov (2015) [15] and Yazdanfar and Öhman (2015) [16]. This result supports Hypothesis 1.…”
Section: Tests Of Hypotheses and Discussionsupporting
confidence: 80%
“…Yazdanfar and Öhman (2015) [17] found that high debt level may increase firms' value in the short run, but result in greater exposure to agency costs and loss of control. Similar findings were also verified by (Maina and Ishmail, 2014) [18].…”
Section: The Relationship Between Financing Decisions and Economic Pementioning
confidence: 99%
“…Vatavu (2014) examined a sample of Romanian listed firms 2003-2012, they were used GMM estimation, and the result of this study was Negative relationship between leverage and profitability. Darush and Peter (2015) examined a of Swedish SMEs firm 2009-2012 they were used Three-stage least squares (3SLS) and fixed-effects models, and the result of this study was Negative relationship between debt ratios (short-term debt and long-term debt) and firm performance (profitability ratios). Chuke et al (2016) examined a sample of Nigeria listed firms 2001-2012, they were used Fixed Effects and Random Effects, and the result of this study was Negative and significant impact owing to limited long term debt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second view finds a negative correlation between debt level and firm performance (Nassar, 2016;Chuke et al, 2016;Darush & Peter, 2015;Vatavu, 2014;Chandrapala & Knapkova, 2013;Iorpev & Kwanum, 2012). These authors used a different methodology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation